Semi-quantitative microplankton analysis (Sylt Roads Time Series) - Wadden Sea off List, Sylt, North Sea in 2022 - Svenja Reents; Johannes J Rick; Marthe Claussen; Malte Elbrächter; Alejandra Castillo-Ramírez; Karen Helen Wiltshire (PANGAEA, 2024)
In order to monitor long-term variability in or eventual change of the planktonic community a semiquantitative analysis of microplankton based on net sampling is ongoing since 1987 in the Sylt-Rømø Bight, a region of high ecological importance within the Marine Protect Area National Park Schleswig Holsteinisches Wattenmeer. The sampling is tightly linked to the LTER Sylt Roads time series thus enabling the coupling of species occurrence to the respective hydrochemical and physical conditions in the water column. These long-term data allow to quantify realized niches of frequently occurring micro-plankton species and to pinpoint rarely occurring species which cannot be detected in the quantitative plankton analysis.